Interference Prevention System Analysis Radio Transmitter Pro 2 Radio Fm Republic Of Indonesia - Puspitasari, Intan; Irwanto, Irwanto (Pusat Publikasi Nusantara, 2022)
Abstract Today, technology is very important in everyday life. Along with the development of technology, there are lots of electronic media that serve to make it easier for humans to get information as part of life, support their activities and fulfill their needs. Information dissemination is carried out through communication media such as mass media. Among the mass media are newspapers and magazines. The technical data analysis used is direct and in-depth observation and interviews and documentation during the time this report is made. With this uplink unit, the broadcast signal that is sent is then changed its beam frequency to be retransmitted (downlink) to one area on earth. Where the radio broadcasting process was first carried out in the studio room, then the results of the audio were received by the audio room which was processed as perfectly as possible so that the radio listener community could hear it